Prioritizing Improvement Among Disadvantaged Students in Principle and in Practice - Joyce, Kathryn (Philosophical Inquiry in Education, 2023)
The US uses an evidence-based approach to education (US-EBE) as a strategy for pursuing two major goals: (1) to raise achievement in the US overall by facilitating improvement among all students, including students in disadvantaged groups; (2) to narrow achievement gaps between socially advantaged and disadvantaged groups by levelling up achievement among disadvantaged students. While both goals prioritize improvement among disadvantaged students in absolute terms, only the second attempts to address unequal achievement by prioritizing improvement among disadvantaged students relative to advantaged students. I argue that US-EBE can be reasonably expected to advance either the first goal or the second goal but not both simultaneously, as intended. This descriptive point raises a normative question: which goal should we pursue using US-EBE? I explore moral considerations that bear on this question, focusing on costs and benefits for students. I argue, provisionally, that we ought to use US-EBE to narrow gaps because the costs associated with doing so are morally justifiable whereas those associated with the alternative are not.